Air Force enlisted force management : system interactions and synchronization strategies - Galway, Lionel A., 1950-; Robbert, Albert A., 1944-; San, Christine; Schiefer, Michael; Stanton, Richard E., 1945- (RAND, 2007)
A fundamental goal of the Air Force personnel system is to ensure that the manpower inventory, by Air Force specialty code and grade, matches requirements. However, there are structural obstacles that impede achieving this goal. The three major independently managed systems the Air Force uses to determine manpower strength currently tend to function in isolation. Because the current organizational structure lacks broad coordinating and control mechanisms, actions taken to control one system often adversely affect another. The authors lay the foundation for a discussion of policy changes that would better synchronize these systems. They propose a methodology that would marginally modify grade authorizations within skill levels to make it possible to better achieve manpower targets. Each specialty would retain the same number of authorizations within each skill level, and the aggregate solution would maintain the same total number of enlisted authorizations by grade. This would help the manpower community follow the policy of equal selection opportunity while also taking personnel management system capabilities into account.